Penerapan Manipulasi Fabric Knife Pleats dan Accordion Pleats pada Streetwear - Nadin Lathifah; Romadhona Chusna Tsani (Garina, 2024)
Along the devolopement of times, technological advances have made changes, including in the field of clothing such as streetwear. This streetwear will be combined with batik materials and also added with manipulating fabric techniques, namely knife pleats and accordion pleats. The problem in this paper is how to apply manipulation of fabric knife pleats and accordion pleats on streetwear? This paper aims to determine the process of applying knife pleats and accordion pleats to streetwear. The method used is a qualitative research method. The process of applying fabric knife pleats and accordion pleats to streetwear begins with designing, measuring the body, making the patterns, forming knife pleats and accordion pleats, merging, to sewing. In making the design, the author combines materials, colors, and shapes. In making knife and accordion pleats, the author applies the same shaping technique but differs in size. Knife pleats will be applied to the wrapped skirt, while accordion pleats are applied to the inner garment. Based on the results of the research on the manipulation of fabric knife pleats and accordion pleats on streetwear that have been completed, the authors found several suggestions when making them, among them are, if you want to use knife pleats, it is better to use plain fabric so that the results of the pleats look clearer. When ironing, both knife pleats and accordion pleats can use the help of pins for a neater look.